INTERNAL CONTROL IN IMPROVING PERFORMANCE AT PAWNSHOP - Hendra Saputra; Ayu Kurnia Sari (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the role of internal control in improving organizational performance at the Pawnshop. The research focuses on evaluating the effectiveness of internal control components, including the control environment, risk assessment, control activities, information and communication, and monitoring. Using qualitative descriptive methods supported by interviews, document analysis, and observations, the study reveals that the internal control system implemented by the Pawnshop has been generally effective in supporting operational efficiency and reducing the risk of errors and fraud. Strong control procedures, clear division of duties, and regular monitoring contribute significantly to improving employee performance and service quality. However, several areas still require improvement, particularly related to technology-based supervision and continuous staff training. Overall, the findings indicate that a well-structured internal control system has a positive impact on enhancing performance at the Pawnshop.